Look-ahead behavior in food culture: the case of Korean food buying - Eri Puspita, Rosana; Dwi Ayuningrum, Anindita Neng Puspa; Zulaikha, Yasinta; Mohd Thas Thaker, Mohamed Asmy (Laboratorium Sosiologi - Program Studi Ilmu Sosiologi, 2022)
The buying behavior of Korean food culture is interesting to study because of its familiarity in Indonesia. The purpose of this study is to determine the buying behavior of traditional Korean food among Indonesian. The research was conducted using a quantitative approach. Data were collected through an online questionnaire from 100 respondents. The results showed that subjective knowledge about Korean food did not affect the purchase intention of Korean food, while the image of the Korean country affected purchasing traditional Korean food. Halal label testing as a moderating variable was carried out in this study. Halal label moderates’ knowledge on purchase intention and does not moderate the Korean image on purchase intention. The new thing offered in this research is the discussion of the cultural invasion that attacks Indonesian.